1999
DOI: 10.1016/s0029-7844(99)00393-2
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-related mortality in Hispanic women in the United States

Abstract: Pregnancy-related mortality ratios for Hispanic women were higher than those for non-Hispanic white women, but markedly lower than those for black women. The similarity in socioeconomic status between Hispanic and black women was not an indicator of similar health outcomes. Prevention of pregnancy-related deaths in Hispanic women should include investigation of medical and nonmedical factors and consider the heterogeneity of the Hispanic population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 6 publications
3
24
0
Order By: Relevance
“…12,21,23 Others, however, did not find a difference in the frequency of the two alleles. [24][25][26] Our findings are similar to those of Hopkins et al 27 who showed a higher frequency of T allele in Hispanic women with PE. A meta-analysis involving 17 studies concluded that C allele homozygotes had a 1.62 times higher risk of developing PE.…”
Section: Discussionsupporting
confidence: 91%
“…12,21,23 Others, however, did not find a difference in the frequency of the two alleles. [24][25][26] Our findings are similar to those of Hopkins et al 27 who showed a higher frequency of T allele in Hispanic women with PE. A meta-analysis involving 17 studies concluded that C allele homozygotes had a 1.62 times higher risk of developing PE.…”
Section: Discussionsupporting
confidence: 91%
“…Despite higher levels of poverty than the other race/ethnicity groups (22% Medicaid insurance vs. 10% for nonHispanic Whites and 18% for non-Hispanic Blacks), Hispanic mothers had significantly longer gestations and better rates of fetal growth. Other researchers have also reported better outcomes in Hispanic mothers compared to non-Hispanic Black mothers, but worse outcomes compared to their non-Hispanic White counterparts (Buekens et al, 2000;Chung et al, 2003;Hessol & Fuentes-Affleck, 2000;Hopkins et al, 1999;Kieffer et al, 1999;Leslie et al, 2003;Scholl et al, 2002). In our study, Hispanic mothers had the highest average birthweight and the longest length of gestation, as well as the lowest proportions of low birthweight, very low birthweight, preterm and early preterm births of the three race/ethnicity groups.…”
Section: Discussionsupporting
confidence: 59%
“…10 The reasons for this excess maternal mortality remain unclear. Whereas few European studies have looked at this subject, 11,12 many studies carried out in the USA have attempted to explain the excess of mortality of the AfricanAmerican women, [13][14][15][16][17] but they used racial categories specific to the US context. More generally, racial or ethnic category does not cover the notion of migration that we have prioritised.…”
Section: Introductionmentioning
confidence: 99%